Antimicrobial Activity of Neutrophils Against Mycobacteria - Parker, Heather A.; Forrester, Lorna; Kaldor, Christopher D.; Dickerhof, Nina; Hampton, Mark B. (Frontiers in Immunology, 2021)
The mycobacterium genus contains a broad range of species, including the human pathogens M. tuberculosis and M. leprae. These bacteria are best known for their residence inside host cells. Neutrophils are frequently observed at sites of mycobacterial infection, but their role in clearance is not well understood. In this review, we discuss how neutrophils attempt to control mycobacterial infections, either through the ingestion of bacteria into intracellular phagosomes, or the release of neutrophil extracellular traps (NETs). Despite their powerful antimicrobial activity, including the production of reactive oxidants such as hypochlorous acid, neutrophils appear ineffective in killing pathogenic mycobacteria. We explore mycobacterial resistance mechanisms, and how thwarting neutrophil action exacerbates disease pathology. A better understanding of how mycobacteria protect themselves from neutrophils will aid the development of novel strategies that facilitate bacterial clearance and limit host tissue damage.